2013
DOI: 10.1002/mrm.25063
|View full text |Cite
|
Sign up to set email alerts
|

Correction of proton resonance frequency shift MR‐thermometry errors caused by heat‐induced magnetic susceptibility changes during high intensity focused ultrasound ablations in tissues containing fat

Abstract: This study has shown the effects of magnetic susceptibility changes induced by heating of breast fatty tissue samples. The resultant errors can be reduced by the use of a model-based correction procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…To mitigate this error, hybrid methods combining the PRF shift and other temperature dependent MR parameters like apparent diffusion coefficient (64) or T1 (34,65,66) are investigated. Multi gradient echoes with variable flip angles allow using the magnitude information for T1 mapping and temperature related T1 changes in lipids and the phase information for PRF thermometry in aqueous tissue (65,66).…”
Section: Magnetic Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…To mitigate this error, hybrid methods combining the PRF shift and other temperature dependent MR parameters like apparent diffusion coefficient (64) or T1 (34,65,66) are investigated. Multi gradient echoes with variable flip angles allow using the magnitude information for T1 mapping and temperature related T1 changes in lipids and the phase information for PRF thermometry in aqueous tissue (65,66).…”
Section: Magnetic Susceptibilitymentioning
confidence: 99%
“…Multi gradient echoes with variable flip angles allow using the magnitude information for T1 mapping and temperature related T1 changes in lipids and the phase information for PRF thermometry in aqueous tissue (65,66). While such hybrid methods are potentially appealing, its propensity to B1 changes as well as temperature dependent M0 and T2* changes reduce T1 mapping accuracy.…”
Section: Magnetic Susceptibilitymentioning
confidence: 99%
“…Many studies have noted that fat‐referenced MR thermometry might have a larger error in tissues with a heterogeneous fat/water distribution, as there is a different magnetic susceptibility distribution between water and fat. However, other studies have shown that this technique works well in tissues with homogeneous fat/water distributions .…”
Section: Discussionmentioning
confidence: 99%
“…A model-based correction procedure for PRF shift thermometry errors caused by heat-induced magnetic susceptibility changes during HIFU ablation in tissues containing fat (breast fatty samples) was proposed by Baron et al 59 A non-parametric temperature controller with non-linear negative reaction for multipoint rapid MRgFUS was proposed by Petrusca et al 60 Experimental methods for improved spatial control of thermal lesions in MRgHIFU ablation were also proposed. 61 Available and accurate methods for retrospective reconstruction of the temperature maps useful in research settings were investigated.…”
Section: Focused Ultrasound Mri and Musculoskeletal Tissues: Pros Anmentioning
confidence: 99%
“…62,63 A recent study by Ramsay et al 64 proposes to monitor temperature changes in the cortical bone using a short echo-time gradient echo sequence. The feasibility of using T 2 mapping to monitor the temperature change in subcutaneous adipose tissue layers was studied by Baron et al 59,65 Temperature monitoring and hyperthermic injury detection in fatty tissue was also tested by using X-ray CT during HIFU thermal treatment. 66 Diakite et al 67 recently presented a three-dimensional segmented echoplanar imaging pulse sequence implementation that simultaneously provides the proton resonance frequency shift temperature of aqueous tissue and the longitudinal relaxation time (T1) of fat during thermal ablation.…”
Section: Focused Ultrasound Mri and Musculoskeletal Tissues: Pros Anmentioning
confidence: 99%